From Nature to Lab: A Review of Secondary Metabolite Biosynthetic Pathways, Environmental Influences, and In Vitro Approaches - Reshi, Zubair Altaf; Ahmad, Waquar; Lukatkin, Alexander S.; Javed, Saad Bin (Metabolites, 2023)
Secondary metabolites are gaining an increasing importance in various industries, such as pharmaceuticals, dyes, and food, as is the need for reliable and efficient methods of procuring these compounds. To develop sustainable and cost-effective approaches, a comprehensive understanding of the biosynthetic pathways and the factors influencing secondary metabolite production is essential. These compounds are a unique type of natural product which recognizes the oxidative damage caused by stresses, thereby activating the defence mechanism in plants. Various methods have been developed to enhance the production of secondary metabolites in plants. The elicitor-induced in vitro culture technique is considered an efficient tool for studying and improving the production of secondary metabolites in plants. In the present review, we have documented various biosynthetic pathways and the role of secondary metabolites under diverse environmental stresses. Furthermore, a practical strategy for obtaining consistent and abundant secondary metabolite production via various elicitation agents used in culturing techniques is also mentioned. By elucidating the intricate interplay of regulatory factors, this review paves the way for future advancements in sustainable and efficient production methods for high-value secondary metabolites.